Hubungan Pemberian MP-ASI Dini Terhadap Kejadian Stunting Pada Balita Di Masa Pandemi Covid-19 Tahun 2022: The Relationship of Early MP-ASI Giving to Stunting Incidents in Toddlers During the Covid-19 Pandemic in 2022 - Riani Widi Astuti; Dina Sulviana Damayanti (Universitas Ngudi Waluyo, 2023)
The golden period of extraordinary child development occurs from 0 to 2 years old. Mother's nutritional status, food priority, duration of exclusive breastfeeding, not eating meat and repeated episodes of diarrhea are variables that determine the occurrence of stunting in children aged 6-59 months. After the baby is born, breast milk is the ideal first meal for babies with very adequate nutritional content for up to 6 months and then continued for up to 24 months with complementary foods (MP-ASI). This study aimed to determine the relationship between early complementary breastfeeding and the incidence of stunting in children aged 6-59 months at Posyandu, East Jakarta. The research design used was descriptive analytics by collecting primary data and observations which were conducted in August 2022. The research sample was taken by purposive sampling at aged 1-5 years with a total of 107 toddlers. Data would be analyzed using the Chi-Square test. This study’s results indicate a significant relationship between early MP-ASI and stunting with a p-value = 0.001. The period of growth and development apart from the physical and mental of the child's brain must also be considered. If a child has nutritional problems such as insufficient nutrition, it can cause developmental delays such as stunting. Keywords: Toodler, MP-ASI, stunting ABSTRAK Periode emas pertumbuhan dan perkembangan anak yang luar biasa terjadi pada usia 0 hingga 2 tahun. Status gizi ibu, prioritas makanan, lama pemberian ASI eksklusif, tidak ada asupan daging dan episode diare berulang merupakan variabel yang menentukan terjadinya stunting pada anak usia 6-59 bulan. Setelah bayi dilahirkan, ASI merupakan makanan pertama yang ideal bagi bayi dengan kandungan nutrisi yang sangat cukup sampai dengan 6 bulan kemudian dilanjutkan sampai 24 bulan dengan makanan pendamping ASI (MP-ASI). Tujuan penelitian ini untuk mengetahui hubungan pemberian MP-ASI dini dengan kejadian stunting pada balita di Posyandu daerah Jakarta Timur. Desain penelitian yang digunakan adalah analitik deskriptif dengan mengumpulkan data primer dan observasi yang dilakukan pada bulan Agustus 2022. Sampel penelitian ini diambil secara purposive sampling pada balita yang berusia 1-5 tahun dengan jumlah 107 balita. Analisis yang digunakan adalah uji Chi Square. Hasil dari penelitian ini menunjukkan hubungan yang signifikan antara pemberian MP-ASI dini dengan terjadinya stunting dengan p-value=0,001. Masa pertumbuhan dan perkembangan fisik, mental, dan otak anak harus diperhatikan. Jika anak memiliki masalah gizi seperti tidak cukup nutrisi, maka dapat menyebabkan keterlambatan perkembangan seperti stunting. Kata Kunci : Balita, MP-ASI, stunting